1981
DOI: 10.1515/znb-1981-1222
|View full text |Cite
|
Sign up to set email alerts
|

In the Search for New Anticancer Drugs, II1 Antitumor Activity, Toxicity and Electron Spin Resonance of Spin Labeled Thio-TEPA Derivatives

Abstract: The spin labeled analog of Thio-Tepa, 1-oxyl-2,2,6,6-tetramethyl-4-piperidyl-N,N;N′,N′−bis (ethylene)−phosphorodiamidothioate (SL−O−TT), which contains a nitroxyl free radical linked by an oxygen bridge to phosphorus, has antitumor properties against P388 murine leukemia (T/C = 242) and a higher therapeutic ratio (5.15) than its parent compound, Thio-TEPA (2.75). The drug is less toxic to P388 cells in culture as judged by the 3H-thymidine uptake. On the basis of electron spin reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1983
1983
1997
1997

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Compounds with a test/control (T/C) percentage greater than 125 or with a percent increase in life span (% ILS) (12) 7a 41 (7.5) 4b 96 (25) 7b34 (15) 5 44 (160) 833(160) 6 27 (20) 7c 16 (20) 14 81(30) 15 48 (30) 16a 29 (10) 16b 23 (10) ILS of 141 at a dose of 6 mg/kg was found to be the most active compound in this group, it is also probably the most toxic. 21 Promising activity was confirmed21 for compounds 4a ( % ILS = 103 at a dose of 12 mg/kg) and 4b (% ILS = 96 at a dose of 25 mg/kg). Although the -type compound 14 was reported to be inactive against the P388 lymphocytic leukemia,19 we found it to be considerable active with a % ILS of 81 at a dose of 30 mg/kg.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Compounds with a test/control (T/C) percentage greater than 125 or with a percent increase in life span (% ILS) (12) 7a 41 (7.5) 4b 96 (25) 7b34 (15) 5 44 (160) 833(160) 6 27 (20) 7c 16 (20) 14 81(30) 15 48 (30) 16a 29 (10) 16b 23 (10) ILS of 141 at a dose of 6 mg/kg was found to be the most active compound in this group, it is also probably the most toxic. 21 Promising activity was confirmed21 for compounds 4a ( % ILS = 103 at a dose of 12 mg/kg) and 4b (% ILS = 96 at a dose of 25 mg/kg). Although the -type compound 14 was reported to be inactive against the P388 lymphocytic leukemia,19 we found it to be considerable active with a % ILS of 81 at a dose of 30 mg/kg.…”
mentioning
confidence: 85%
“…Distillation of the remaining oil (6.4 g) gave 5.4 g (50%) of lib: bp 82-84 °C (15 mm); n25D 1.4656. The compound was found to be pure by TLC, Rf 0.5 (neutral alumina; benzene/methylene chloride/methanol, 4:4:0.5, v/v) and GLC (injection 190 °C, column 185 °C, detector 215 °C); IR (neat) 3250 (NH) cm'1; MS, m/e 171 (M+ + 1,100), 140 (49), 83 (21);…”
Section: Methodsmentioning
confidence: 99%
“…The attachment of nitroxyl compounds to anticancer agents presents the attractive possibility of monitoring by EPR spectroscopy the interaction of the drugs with various cell biopolymers, such as, DNA, RNA, proteins, lipids, and carbohydrates, as well as their metabolism and tissue distribution. It was shown that while the nitroxyl moiety imparts a beneficial influence on the anticancer properties of a drug, ,− the nitroxyl group by itself has no anticancer activity, , is relatively nontoxic, is not carcinogenic or mutagenic, , exhibits no synergistic effect, and has little effect on the cell growth and the cell cycle kinetics . These facts can be explained , by assuming that the nitroxyl radical is a carrier group which facilitates the transport of the drug through the biological membranes to the cellular DNA.…”
Section: G Nitroxyl (Aminoxyl) Analogsmentioning
confidence: 99%
“…Thus the covalent bonding of a nitroxyl group to anticancer agents could result in an increase in the therapeutic index, i.e. a broader range of safe doses …”
Section: G Nitroxyl (Aminoxyl) Analogsmentioning
confidence: 99%
“…Recently, we reported [1] concerning the antitumor activity of two spin labeled analogs of the clinically used Thio-TEPA (1). Thus, SL-O-TT (2) and SL-NH-TT (3) [2] were evaluated, in accordance with the protocol [3], in vivo against lymphocytic P 388 murine leukemia.…”
Section: Introductionmentioning
confidence: 99%